2007
DOI: 10.1007/s10661-007-9616-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of on-site sanitation on groundwater contamination in basaltic environment ’A case study from India

Abstract: On-site sanitation is increasingly adopted in urban cities in India. The adoption of on-site sanitation system puts the groundwater resources in the vicinity of the system at a greater risk. Microbial contaminants as well as chemical contaminants like Chloride and Nitrate are generated from human waste. These contaminants travel through the medium and ultimately get in contact with the groundwater. Hence, the groundwater sources are vulnerable to nitrate contamination near the on-site sanitation systems. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…Also, direct access of livestock to canal water in rural areas is an important source of potential pathogens in water. According to Pujari et al (2007), the on-site sanitation that is increasingly adopted in India is possibly responsible for high levels of nitrates and bacterial contamination in drinking water sources. In rural areas, people prefer to eliminate night soils in open places especially in agriculture fields.…”
Section: Fig 2 Occurrences Of Bacterial Species In Water Samplesmentioning
confidence: 99%
“…Also, direct access of livestock to canal water in rural areas is an important source of potential pathogens in water. According to Pujari et al (2007), the on-site sanitation that is increasingly adopted in India is possibly responsible for high levels of nitrates and bacterial contamination in drinking water sources. In rural areas, people prefer to eliminate night soils in open places especially in agriculture fields.…”
Section: Fig 2 Occurrences Of Bacterial Species In Water Samplesmentioning
confidence: 99%
“…Among the anthropogenic factors, the impact of on-site sanitation on groundwater quality has been a subject of much concern. The contamination of groundwater due to on-site sanitation systems has been reported by different authors since the 1980s (Lu et al 2008;Pujari et al 2007;Dzwairo et al 2006;NEERI report 2005;Nsubuga et al 2004;Lawrence et al 2001;Chidavaenzi et al 2000;Mallard et al 1994;Andrews 1988;Canter and Knox 1985;Hagedon 1984;Dewalle and Schaff 1980;Lewis et al 1980;Brown et al 1979). It is reported that 25% of all housing units in the USA have on-site sanitation systems (Bunnels et al 1999) and they are reported to be source of local and regional groundwater contamination in USA and elsewhere (Bunnels et al 1999;Clawges and Vowinkel 1996).…”
Section: Introductionmentioning
confidence: 96%
“…The existence of elements with higher poisoning levels in groundwater is related to the disposal of industrial wastewater containing nitrogen (N) [3][4][5]. Groundwater pollution by sewage has been reported by many researchers [6][7][8][9][10]. Such contamination has led to serious problems in areas where groundwater is the main source of drinking water consumption.…”
Section: Introductionmentioning
confidence: 99%